1995
DOI: 10.1172/jci117745
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neutrophil influx in glomerulonephritis in the rat with anti-macrophage inflammatory protein-2 (MIP-2) antibody.

Abstract: The role of the chemokine, macrophage inflammatory protein-2 (MIP-2), during anti-glomerular basement membrane (GBM) antibody (Ab) glomerulonephritis (GN) was studied. Rat MIP-2 cDNA had been cloned previously. Recombinant rat MIP-2 (rMIP-2) from Escherichia coli exhibited neutrophil chemotactic activity and produced neutrophil influx when injected into the rat bladder wall. By using a riboprobe derived from the cDNA and an anti-rMIP-2 polyclonal Ab, MIP-2 was found to be induced in glomeruli with anti-GBM Ab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 64 publications
7
121
0
Order By: Relevance
“…Chemokines mediate leukocyte migration into the injured kidney and IFN-␥ modulates chemokine production, including IFN-␥-inducing protein 10 (IP-10), monokine-induced by IFN-␥, and IFN-␥-inducible T cell chemoattractant production, which bind to CXCR3 to mediate T cell migration (25) (25)(26)(27)(28)(29)(30). Our previous study showed that renal IRI up-regulated IP-10 and MIP␣, MIP1␤, MIP2, which are thought to mediate T cell and neutrophil migration (31,32). The source of increased IFN-␥ production upon stimulation by IL-12 is mainly from Th1, NKT (14,33,34), and myeloid cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines mediate leukocyte migration into the injured kidney and IFN-␥ modulates chemokine production, including IFN-␥-inducing protein 10 (IP-10), monokine-induced by IFN-␥, and IFN-␥-inducible T cell chemoattractant production, which bind to CXCR3 to mediate T cell migration (25) (25)(26)(27)(28)(29)(30). Our previous study showed that renal IRI up-regulated IP-10 and MIP␣, MIP1␤, MIP2, which are thought to mediate T cell and neutrophil migration (31,32). The source of increased IFN-␥ production upon stimulation by IL-12 is mainly from Th1, NKT (14,33,34), and myeloid cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…MDC riboprobe was synthesized with incorporation of 35 S-UTP as previously described. 10 Following in situ hybridization and before dehydration, the slides were incubated for 5 minutes in Tris-buffered saline. Endogenous peroxidase, avidin, and biotin were inactivated, and then sections were incubated with mAb ED-1 or mAb CD8a and with peroxidaseconjugated goat anti-mouse IgG, followed by mouse PAP.…”
Section: In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%
“…Based on the structure (33,34) and calculations of the difference in solvent accessibility between monomer and dimer, we identified several candidates for mutation including Tyr 13 , Thr 10 , Val 9 , and Pro 8 ( Fig. 1).…”
Section: Y13a* Affects Receptormentioning
confidence: 99%
“…These residues form a short stretch of ␤-sheet at the interface between the two subunits. Tyr 13 and Tyr 13 Ј are oriented toward each other and in the crystal structure (34) are hydrogen bonded through an intervening water molecule. They also make hydrophobic contacts that stabilize the dimer by packing onto Val 9 of the opposing subunit.…”
Section: Y13a* Affects Receptormentioning
confidence: 99%
See 1 more Smart Citation